2011
DOI: 10.1002/jccs.201190077
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐flotation Separation of Cd(II), Co(II) and Pb(II) Traces Using a New Ligand before Their Flame Atomic Absorption Spectrometric Determinations in Colored Hair and Dryer Agents of Paint

Abstract: A simple, rapid and inexpensive method for separation and preconcentration of some traces of hazardous elements is presented prior to their flame atomic absorption spectrometric determinations. At pH 6.5; cadmium(II), cobalt(II) and lead(II) were separated simultaneously with 1,2-bis((1H-benzo[d]imidazol-2-yl)methoxy)benzene (BBIMB) as a new complexing agent and floated after adding sodium dodecyl sulfate (SDS) as a foaming reagent. The floated layer was then eluted by concentrated nitric acid in methanol and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Moreover, PbCl remained undissociated as H 2 PbCl 4 at lower pH condition and it further inhibits complexation of solute with carrier [22]. Similar results were reported by other researchers too [23,24]. Both the extraction and recovery start decreasing beyond the pH of 5.0 when sufficient HCl is unavailable for the protonation.…”
Section: Determination Of Appropriate Operating Range Of Ph In Feed Ssupporting
confidence: 88%
“…Moreover, PbCl remained undissociated as H 2 PbCl 4 at lower pH condition and it further inhibits complexation of solute with carrier [22]. Similar results were reported by other researchers too [23,24]. Both the extraction and recovery start decreasing beyond the pH of 5.0 when sufficient HCl is unavailable for the protonation.…”
Section: Determination Of Appropriate Operating Range Of Ph In Feed Ssupporting
confidence: 88%
“…In various separation and preconcentration studies (34)(35)(36)(37)(38)(39) it has been reported that complexation of metal ions with a suitable chelating agent improves the recoveries of the analyte ions. In our study, we examined the influence of different Brillant Black BN amounts on the recoveries of Pb(II) on the cellulose nitrate membrane filter while keeping other parameters constant.…”
Section: Effect Of Amount Of Brillant Black Bmmentioning
confidence: 99%
“…[1][2][3][4][5][6] Hence, a simple, sensitive and powerful method is necessary to determine silver at trace and ultra-trace levels. The direct determination of silver in complex matrix by common methods, such as flame atomic absorption spectrometry (FAAS), 7 electrothermal atomic absorption spectrometry (ETAAS), 8 neutron activation analysis (NAA), 9 inductively coupled plasma atomic emission spectrometry (ICP-AES), 10 is usually difficult because of low concentration of silver and matrix interference and an initial sample pretreatment is necessary. Several different methods, such as liquid-liquid extraction (LLE), 11 cloud point extraction (CPE), 12 and solid phase extraction (SPE), 13,14 have been used for this purpose.…”
Section: Introductionmentioning
confidence: 99%